Walking-based activity and sedentary behavior in Saudi males with chronic obstructive pulmonary disease - Alyami, M.; Jenkins, Susan; Hill, Kylie (2018)
© 2018, Saudi Arabian Armed Forces Hospital. All rights reserved. Objectives: To compare walking-based activity and sedentary behavior between males with chronic obstructive pulmonary disease (COPD) and healthy controls and to examine the association between dyspnea with time spent in walking-based activity and sedentary behavior in males with COPD. Methods: This cross-sectional study of 30 males with COPD (age 62.0±5.0 years; forced expiratory volume in one second [FEV1] 46±15% predicted) and 29 healthy controls (age 63.0±4.3 years; FEV1 91±5% predicted) was conducted at the outpatient pulmonary clinics at King Fahad Medical City, Riyadh, Kingdom of Saudi Arabia between February 2013 and March 2014. Walking-based activity and sedentary behavior were evaluated using an activity monitor. Results: Participants with COPD spent less time engaged in walking-based activity (22±8% versus 37±7% of waking hours; p<0.001) and more time engaged in sedentary behavior (78±8% versus 63±6% of waking hours; p<0.001) than healthy controls. In males with COPD, moderate to strong associations were found between the scores of the quality and emotional response components of the Dyspnea-12 (D-12) questionnaire and time spent engaged in walking-based activity and sedentary behavior (r: =0.46, all p<0.01). Conclusion: Males with COPD were less active and more sedentary than healthy controls. The D-12 components were associated with walking-based activity and sedentary behavior in males with COPD.